Electrode mixture for roll molding, method for manufacturing electrode active material layer, and method for manufacturing electrode

The roll molding electrode mixture with a tailored composition addresses the issues of active material damage and sticking during the roll molding process, enhancing the durability and performance of the electrodes by dispersing the load and maintaining the right balance of solid and solvent content.

JP7666267B2Active Publication Date: 2025-04-22TOYOTA INDUSTRIES CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021156369
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-27
Publication Date
2025-04-22
Estimated Expiration
2041-09-27

AI Technical Summary

Technical Problem

During roll molding of electrode mixtures for nonaqueous electrolytic secondary batteries, the high load applied can cause the active material to be crushed or broken, and increasing the solvent content can lead to sticking issues and prevent successful roll molding.

Method used

A roll molding electrode mixture with a specific composition, containing an electrode active material with a TAP density of 1.3 g/cm³ and an oil absorption amount of 40 mL/100 g to 80 mL/100 g, and a solid content ratio of 70% to 80% by mass and a solvent ratio of 20% to 30% by mass, is used to reduce the load on the active material and prevent sticking.

Benefits of technology

This composition effectively suppresses damage to the electrode active material during roll molding, prevents cracking and migration of the active material layer, and improves the durability and performance of the electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666267000002
    Figure 0007666267000002
  • Figure 0007666267000001
    Figure 0007666267000001
Patent Text Reader

Abstract

To suitably suppress the breakage of an electrode active material contained in a roll-forming electrode mixture, and improve the battery performance.SOLUTION: A roll-forming electrode mixture contains a solid content containing an electrode active material and a solvent. The electrode active material has a TAP density of 1.3 g / cm3 or less, an oil absorption of 40 mL / 100 g or more and 80 mL / 100 g or less, and a solid content of 70 mass% or more and 80 mass% or less, and a solvent at a ratio of 20 mass% or more and 30 mass% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrode binder for roll forming, a method for manufacturing an electrode active material layer, and a method for manufacturing an electrode.

Background Art

[0002] Patent Document 1 describes a non-aqueous electrolyte secondary battery including an active material layer containing an active material, a conductive material, and a binder on a current collector. It is described that the relationship between the DBP oil absorption amount A of the conductive material contained in the central portion of the active material layer and the DBP oil absorption amount B of the conductive material contained in the first and second end portions is 100 ≦ B < A ≦ 450 (mL / 100 g). By the oil absorption amount of the conductive material being within the above numerical range, the depletion of the non-aqueous electrolyte solution and the occurrence of uneven salt concentration during high-rate charge and discharge are suppressed, and the high-rate cycle characteristics are improved.

Prior Art Documents

Patent Documents

[0003]

Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0004] By the way, an electrode such as a non-aqueous electrolyte secondary battery is manufactured, for example, by roll-forming a binder containing an active material and a solvent on a current collector and crimping it to the current collector. During roll forming, a relatively large load is applied to the binder, so depending on the load, the active material contained in the binder may be pulverized or broken, and there is a risk of damage to the active material. If the content of the solvent in the binder is increased to reduce the load, the binder is likely to stick to the roll, and there is a risk that roll forming cannot be performed.

Means for Solving the Problems

[0005] The electrode mixture for roll molding that achieves the above object is an electrode mixture for roll molding that contains a solid content including an electrode active material and a solvent, and the electrode active material has a TAP density of 1.3 g / cm 3 The oil absorption is 40 mL / 100 g or less and 80 mL / 100 g or less, the solid content is 70 mass % or more and 80 mass % or less, and the solvent is 20 mass % or more and 30 mass % or less.

[0006] In the electrode mixture for roll molding which achieves the above object, the electrode active material is a negative electrode active material, and the electrode mixture is used for producing a negative electrode. A method for producing an electrode active material layer that achieves the above object includes a forming step of roll-forming an electrode layer using the above electrode mixture for roll forming, and a drying step of drying the electrode layer.

[0007] The method for producing an electrode active material layer that achieves the above object is used for producing a negative electrode active material layer, in which the electrode layer is a negative electrode layer. A method for producing an electrode that achieves the above object includes a forming step of roll-forming an electrode layer on a current collector using the above electrode mixture for roll forming, and a drying step of drying the electrode layer.

[0008] The method for producing an electrode that achieves the above object is used to produce a negative electrode, wherein the electrode layer is a negative electrode layer. Effect of the Invention

[0009] According to the present invention, damage to an electrode active material contained in an electrode mixture for roll molding can be suitably suppressed, and battery performance can be improved. [Brief description of the drawings]

[0010] [Figure 1] FIG. 2 is an end view of the electrode forming apparatus. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. The wet powder as the electrode mixture for roll molding contains a solid content including an electrode active material and a solvent.

[0012] As shown in Fig. 1, the wet powder P is rolled into a sheet using an electrode forming device 1, and is pressed against a long strip-shaped current collector foil 50 as a current collector to form an electrode layer 60. The electrode layer 60 is then dried to separate the solvent, forming an electrode active material layer. An electrode is formed by the current collector foil 50 and the electrode active material layer.

[0013] The wet powder P will be described below. <Wet powder P> The wet powder P is a material with poor fluidity that contains a solid content including an electrode active material and a solvent. The solid content is a material that remains after the solvent is separated from the wet powder P by drying or the like. The solid content is not particularly limited, but may contain a binder and a conductive assistant in addition to the electrode active material.

[0014] When the wet powder P is granulated, the particle size of the granulated wet powder is preferably 3 mm or less. The lower limit of the particle size is preferably 500 μm. The particle size can be calculated by image analysis or the like. Specifically, the diameter of the circumscribed circle of a wet powder image taken under a microscope can be taken as the particle size of the wet powder P. In this specification, unless otherwise specified, the wet powder P refers to both granulated and non-granulated powder.

[0015] The electrode active material has a TAP density of 1.3 g / cm 3 The oil absorption is 40 mL / 100 g or more and 80 mL / 100 g or less, the solid content is 70 mass % or more and 80 mass % or less, and the solvent content is 20 mass % or more and 30 mass % or less.

[0016] The tap density is 1.25 g / cm 3 It is preferable that the density is 1.2 g / cm or less. 3 More preferably, the TAP density is 0.9 g / cm or less.3 It is preferable that the content is 1.0 g / cm or more. 3 More preferably, it is equal to or greater than this.

[0017] When the TAP density is in the above-mentioned range, the load applied to the wet powder P during roll molding can be dispersed among the electrode active materials, thereby reducing the load applied to the electrode active materials.

[0018] The electrode active material preferably has an oil absorption of 45 mL / 100 g or more, more preferably 50 mL / 100 g or more, and preferably has an oil absorption of 77 mL / 100 g or less, more preferably 75 mL / 100 g or less.

[0019] When the oil absorption of the electrode active material is 40 mL / 100 g or more and 80 mL / 100 g or less, the electrode active material can favorably retain the solvent. The TAP density and oil absorption of the electrode active material vary depending on the type of electrode active material. For example, the values ​​vary depending on the shape, surface area, porosity, pore size, etc. of the electrode active material. Therefore, the TAP density and oil absorption can be adjusted by selecting the type of electrode active material to be used.

[0020] When the solid content of the wet powder P is 70% by mass or more, the wet powder P can be prevented from sticking to the roll during roll molding. Also, when the solid content is 80% by mass or less, cracks in the active material layer after roll molding can be prevented.

[0021] (Method of measuring TAP density) The method for measuring the TAP density is not particularly limited, and any known measuring method can be used. Examples of the method for measuring the TAP density include the following method.

[0022] First, prepare a 100 mL measuring cylinder. After measuring the mass of the measuring cylinder, pour the sufficiently dried electrode active material into the measuring cylinder. Measure the mass of the measuring cylinder into which the electrode active material has been poured, and calculate the mass M of the electrode active material.

[0023] The opening of the measuring cylinder is sealed with a rubber stopper. The measuring cylinder is allowed to drop naturally onto the rubber plate from a height of about 5 cm above the rubber plate. The action of allowing the cylinder to drop naturally onto the rubber plate is also called tapping. After tapping is performed 250 times, the volume V of the electrode active material in the measuring cylinder is measured.

[0024] The TAP density is calculated by dividing the mass M of the electrode active material by the volume V of the electrode active material. (Method of measuring oil absorption) The method for measuring the oil absorption is not particularly limited, and a known measuring method can be used. For example, the oil absorption can be measured according to the procedure described in "JIS K 6217-4 (Carbon black for rubber-Basic properties-Part 4: Determination of oil absorption (including compressed samples))".

[0025] Each material constituting the wet powder P will be described below. (electrode active material) The electrode active material means a positive electrode active material or a negative electrode active material. That is, the electrode mixture for roll molding containing a positive electrode active material means a positive electrode mixture for roll molding. The electrode mixture for roll molding containing a negative electrode active material means a negative electrode mixture for roll molding.

[0026] (Negative electrode active material) The negative electrode active material is a material capable of absorbing and releasing charge carriers. The negative electrode active material is not particularly limited, and may be, for example, an element, an alloy, or a compound capable of absorbing and releasing charge carriers such as lithium ions.

[0027] Examples of the simple substance include Group 14 elements such as lithium, carbon, silicon, germanium, and tin, and Group 13 elements such as aluminum and indium. Examples of the simple substance include Group 12 elements such as zinc and cadmium, Group 15 elements such as antimony and bismuth, alkaline earth metals such as magnesium and calcium, and Group 11 elements such as silver and gold.

[0028] Examples of the alloy include tin-based materials such as Ag-Sn alloy, Cu-Sn alloy, and Co-Sn alloy. Examples of the above compounds include carbonaceous materials such as various graphites, silicon-based materials such as silicon elemental and SiOx (0.3≦x≦1.6) which are disproportionated to silicon dioxide, and composites of silicon elemental or silicon-based materials and carbonaceous materials.

[0029] The above compounds include Nb2O5, TiO2, Li4Ti5O 12 Alternatively, oxides such as WO2, MoO2, Fe2O3, or nitrides represented by Li3-xMxN (M=Co, Ni, Cu) may be used.

[0030] The negative electrode active material may be used alone or in combination of two or more. Among these, graphite is preferred because it is easy to improve the electrical conductivity. (Cathode active material) The positive electrode active material is a material capable of absorbing and releasing charge carriers. The positive electrode active material is not particularly limited, but may be, for example, a lithium composite metal oxide Li2MnO3 having a layered rock salt structure and represented by the general formula: LiaNibCocMndDeOf (0.2≦a≦2, b+c+d+e=1, 0≦e<1, 1.7≦f≦3, D is at least one element selected from W, Mo, Re, Pd, Ba, Cr, B, Sb, Sr, Pb, Ga, Al, Nb, Mg, Ta, Ti, La, Zr, Cu, Ca, Ir, Hf, Rh, Fe, Ge, Zn, Ru, Sc, Sn, In, Y, Bi, S, Si, Na, K, P, and V).

[0031] In addition, examples of the positive electrode active material include metal oxides with a spinel structure such as LiMn2O4, solid solutions composed of a mixture of metal oxides with a spinel structure and layered compounds, and polyanion compounds represented by LiMPO4, LiMVO4, Li2MSiO4 (wherein M is at least one selected from Co, Ni, Mn, and Fe), etc.

[0032] Positive electrode active materials include tavorite-based compounds represented by LiMPO4F (M is a transition metal), such as LiFePO4F, and borate-based compounds represented by LiMBO3 (M is a transition metal), such as LiFeBO3.

[0033] Any metal oxide used as a positive electrode active material may have the above composition formula as its basic composition, and metal elements contained in the basic composition may be replaced with other metal elements. The electrode active material of this embodiment may be either a positive electrode active material or a negative electrode active material, but is preferably a negative electrode active material. In general, the load of roll forming when making a negative electrode is larger than the load of roll forming when making a positive electrode. Since the negative electrode active material is more likely to break, if the electrode active material is a negative electrode active material, breakage due to the load during roller forming can be more effectively suppressed.

[0034] (Binding agent) The binder has a function of binding the current collector foil 50 and the electrode layer 60. The binder may also have a function as a dispersant that improves the dispersibility of the electrode active material and the like in the wet powder P.

[0035] The type of binder is not particularly limited. Specific examples of the binder include rubber such as styrene-butadiene rubber (hereinafter also referred to as SBR), fluorine-containing resins such as polyvinylidene fluoride, polytetrafluoroethylene, and fluorine-containing rubber, and thermoplastic resins such as polypropylene and polyethylene.

[0036] Other examples include imide resins such as polyimide and polyamideimide, alkoxysilyl group-containing resins, and acrylic resins containing monomer units such as acrylic acid and methacrylic acid. Furthermore, a polymer having a hydrophilic group may be used. Examples of the hydrophilic group of the polymer having a hydrophilic group include a carboxyl group, a sulfo group, a silanol group, an amino group, a hydroxyl group, and a phosphate group.

[0037] Specific examples of polymers having hydrophilic groups include polyacrylic acid and carboxymethyl cellulose (hereinafter also referred to as CMC). Specific examples of polymers having hydrophilic groups include polymers containing carboxyl groups in the molecule, such as polymethacrylic acid, or polymers containing sulfo groups, such as poly(p-styrenesulfonic acid). Specific examples of polymers having hydrophilic groups include polyvinylpyrrolidone and polyvinyl alcohol. Polymers containing many carboxyl groups and / or sulfo groups, such as polyacrylic acid or copolymers of acrylic acid and vinylsulfonic acid, are water-soluble.

[0038] The polymer having a hydrophilic group is preferably a water-soluble polymer, and in terms of chemical structure, is preferably a polymer containing a plurality of carboxyl groups and / or sulfo groups in one molecule. The binders may be used alone or in combination of two or more.

[0039] The content of the binder in the solid content of the wet powder P is not particularly limited, but is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more. Also, it is preferably 10% by mass or less, more preferably 6% by mass or less, and even more preferably 4% by mass or less.

[0040] (Conductive assistant) The conductive additive is a chemically inactive high electron conductor. The chemically inactive electron highly conductive material is not particularly limited, but examples thereof include carbon black, which is a carbonaceous fine particle, graphite, vapor-grown carbon fiber, carbon nanotubes (hereinafter also referred to as CNT), various metal particles, etc. Examples of carbon black include acetylene black, Ketjen Black (registered trademark), furnace black, channel black, etc.

[0041] The conductive assistant may be used alone or in combination of two or more kinds. The content of the conductive assistant in the solid content of the wet powder P is not particularly limited, but is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more. Also, it is preferably 3% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less.

[0042] (solvent) The solvent is mixed with the solids to impart wettability to the solids, which imparts fluidity to the wet powder P that allows roll molding.

[0043] The solvent is not particularly limited, but examples thereof include water, N-methyl-2-pyrrolidone, alcohol, and the like. The above solvents may be used alone or in combination of two or more.

[0044] (Method of preparing wet powder P) The method for preparing the wet powder P is not particularly limited. It can be prepared by mixing each material constituting the solid content with a solvent. A part of the material may be mixed with the solvent first, and the remaining material may be added and mixed later. The solvent content may be mixed in advance to a large amount, and the mixture may be heated while mixing or heated after mixing to adjust the solvent content to a predetermined amount.

[0045] Hereinafter, the current collector which constitutes the electrode together with the electrode active material layer will be described. <Current collector> The shape of the current collector foil 50 as a current collector is not particularly limited, but the thickness is usually 1 mm or less. The width and length of the current collector foil 50 are greater than the thickness. The current collector foil 50 has a first surface S1 on one side in the thickness direction and a second surface S2 on the other side in the thickness direction.

[0046] The electrode forming apparatus 1 forms an electrode layer 60 on a first surface S1 of the current collector foil 50. The electrode forming apparatus 1 will now be described. <Configuration of electrode forming device 1> As shown in FIG. 1, the electrode forming apparatus 1 includes a first driving roll 11 and a second driving roll 12. The electrode forming apparatus 1 also includes a supply roll 80 that supplies the current collecting foil 50, and a take-up roll 90 that takes up the current collecting foil 50 supplied from the supply roll 80. The electrode forming apparatus 1 also includes a wet powder supplying device 95 that supplies wet powder P to the current collecting foil 50 passing between the first driving roll 11 and the second driving roll 12. The electrode forming apparatus 1 also includes a drying device (not shown) below the second roll 12 that dries the current collecting foil 50 on which the electrode layer 60 has been formed. The drying device is not particularly limited, and a known hot air drying oven, IR drying oven, hot plate, heat roll, etc. can be used.

[0047] The first driving roll 11 and the second driving roll 12 are made of metal. The first driving roll 11 and the second driving roll 12 have the same diameter and length. The axes of the first driving roll 11 and the second driving roll 12 extend in the same direction and are parallel to each other.

[0048] The first driving roll 11 has a first roll portion 111 and two first shaft portions 112. The diameter of the first roll portion 111 is larger than the diameters of the two first shaft portions 112. One of the first shaft portions 112 is provided at one end of the first roll portion 111 in the longitudinal direction, and the other first shaft portion 112 is provided at the other end of the first roll portion 111 in the longitudinal direction. The axis of the first roll portion 111 and the axis of the two first shaft portions 112 coincide with each other.

[0049] The second driving roll 12 has a second roll portion 121 and two second shaft portions 122. The diameter of the second roll portion 121 is larger than the diameters of the two second shaft portions 122. One second shaft portion 122 is provided at one end of the second roll portion 121 in the longitudinal direction, and the other second shaft portion 122 is provided at the other end of the second roll portion 121 in the longitudinal direction. The axis of the second roll portion 121 and the axis of the two second shaft portions 122 coincide with each other.

[0050] The two first shaft portions 112 are fixed to a first fixed base (not shown) via bearings. The first driving roll 11 is supported rotatably with respect to the first fixed base. The two second shaft portions 122 are fixed to a second fixed base (not shown) via bearings. The second driving roll 12 is supported rotatably with respect to the second fixed base.

[0051] The positions of the first driving roll 11 and the second driving roll 12 can be adjusted so as to be close to or spaced apart from each other. The first drive roll 11 and the second drive roll 12 are rotated by a power unit (not shown) such that the first drive roll 11 rotates in the opposite direction to the second drive roll 12. The peripheral speed of the second drive roll 12 is faster than that of the first drive roll 11. The current collector foil 50 is transported at the same speed as the peripheral speed of the second drive roll 12.

[0052] The method for producing the electrodes will be described below. <Electrode manufacturing method> The method for manufacturing the electrode includes a forming step of roll-forming the electrode layer 60 on the current collector foil 50 using an electrode mixture for roll forming, and a drying step of drying the electrode layer 60.

[0053] (molding process) As shown in FIG. 1, the current collector foil 50 is fed from a supply roll 80 of the electrode forming apparatus 1 and passed between a first driving roll 11 and a second driving roll 12.

[0054] Wet powder P is continuously supplied from a supply port of a wet powder supplying device 95 to the current collector foil 50 passing between the first driving roll 11 and the second driving roll 12 . The rotation of the first driving roll 11 presses the wet powder P toward the first surface S1 of the current collecting foil 50. The wet powder P is also pressed in the thickness direction of the current collecting foil 50 by the first driving roll 11 and the second driving roll 12. By pressing the wet powder P against the first surface S1 of the current collecting foil 50, the wet powder P is pressure-bonded to the first surface S1 of the current collecting foil 50, and an electrode layer 60 is formed on the first surface S1 of the current collecting foil 50.

[0055] Incidentally, in the electrode layer 60 immediately after passing between the first driving roll 11 and the second driving roll 12, the solvent contained in the wet powder P has not been separated yet. In other words, the solvent has not been removed yet.

[0056] The electrode layer 60 immediately after passing between the first driving roll 11 and the second driving roll 12 is also referred to as a precursor of an electrode active material layer. The electrode layer 60 is formed over the entire length in the longitudinal direction of the current collector foil 50. The current collector foil 50 on which the electrode layer 60 has been formed is transported downstream of the first driving roll 11 and the second driving roll 12 in the transport direction D.

[0057] The thickness of the electrode layer to be formed is, for example, 100 μm or more. For example, when forming a negative electrode layer, the thickness can be 150 μm or more, or even 200 μm or more, and when forming a positive electrode layer, the thickness can be 300 μm or more, or even 500 μm or more.

[0058] (drying process) The current collector foil 50 on which the electrode layer 60 is formed is dried in a drying device to separate the solvent contained in the electrode layer 60. The drying temperature is not particularly limited, but is preferably 50° C. or higher and 100° C. or lower.

[0059] After the drying process, the current collector foil 50 is wound up on a winding roll 90. By separating the solvent, an electrode active material layer is formed on the current collector foil 50. The current collector foil 50 and the electrode active material layer form an electrode. By going through the above steps, an electrode can be manufactured.

[0060] The operation of this embodiment will be described. The TAP density of the electrode active material is 1.3 g / cm 3 By satisfying the above condition, the electrode active material is relatively bulky and has many gaps between the electrode active materials. The load applied to the wet powder P during roll molding can be dispersed among the electrode active materials, thereby reducing the load applied to the electrode active material. In other words, it is possible to avoid the load being applied directly to the electrode active material.

[0061] In addition, when the oil absorption of the electrode active material is 40 mL / 100 g or more and 80 mL / 100 g or less, the electrode active material can retain the solvent favorably. Specifically, when the oil absorption is 40 mL / 100 g or more, the wet powder P can retain a larger amount of solvent. Therefore, cracking of the active material layer after roll molding can be suppressed.

[0062] Furthermore, when the oil absorption is 80 mL / 100 g or less, it is possible to prevent the amount of solvent held by the wet powder P from becoming too large. This can prevent the active material layer from easily peeling off from the current collector foil 50 due to separation of the solvent, also known as migration, that occurs after roll forming, which would otherwise occur if the amount of solvent held becomes too large. Furthermore, it is possible to prevent the wet powder P from sticking to the roll during roll forming.

[0063] Moreover, the wet powder P has a solid content of 70% by mass or more. In the case of conventional wet powders, the solid content generally exceeds 80% by mass. In contrast, in this embodiment, by using an electrode active material having the above-mentioned oil absorption amount, even in a range where the solid content is relatively small, the wet powder P can be prevented from sticking to the roll and roll molding can be performed. Since the solid content is relatively small, the load during roll molding can be reduced. Furthermore, since the solid content is 80% by mass or less, cracking of the active material layer after roll molding can be suppressed.

[0064] The effects of this embodiment will be described. (1) The electrode active material has a TAP density of 1.3 g / cm 3 The oil absorption is 40 mL / 100 g or more and 80 mL / 100 g or less, the solid content is 70 mass % or more and 80 mass % or less, and the solvent content is 20 mass % or more and 30 mass % or less.

[0065] During roll molding, the load applied to the wet powder P can be reduced while preventing the wet powder P from sticking to the roll. Therefore, damage to the electrode active material can be suitably prevented. In addition, since cracking and migration of the active material layer after roll molding can be prevented, the durability of the electrode can be improved, and the battery performance can be improved.

[0066] (2) The electrode active material is a negative electrode active material and is used to manufacture a negative electrode. Since a negative electrode active material such as graphite is a material that is relatively more susceptible to damage than a positive electrode active material, when the electrode active material is a negative electrode active material, damage caused by the load during roller forming can be suitably suppressed.

[0067] <Example of change> This embodiment can be modified as follows: This embodiment and the following modifications can be combined with each other to the extent that no technical contradiction occurs.

[0068] In the present embodiment, the electrode forming apparatus 1 includes a drying device, but is not limited to this. The electrode forming apparatus 1 does not have to include a drying device. A drying device may be prepared separately from the electrode forming apparatus 1, and the current collecting foil on which the electrode layer 60 is formed may be dried using this drying device. In other words, the electrode forming apparatus 1 is not limited to the configuration shown in FIG. 1.

[0069] In the present embodiment, the electrode layer 60 is formed on the first surface S1 of the current collecting foil 50, but this is not limiting. The electrode layer 60 may be formed on the second surface S2 of the current collecting foil, or may be formed on both the first surface S1 and the second surface S2. In an embodiment in which the electrode layer 60 is formed on both the first surface and the second surface, a hyperbolic electrode, also known as a bipolar electrode, may be formed.

[0070] In the present embodiment, the wet powder P is roll-formed on the current collector foil 50, but the present invention is not limited to this. The wet powder P may be roll-formed into a sheet by itself. After roll-forming, the wet powder P may be dried to form an electrode active material layer. That is, the present invention may be an invention of a method for producing an electrode active material layer.

[0071] The wet powder P may be rolled into a sheet by itself, dried, and then laminated to the current collector foil 50 to produce an electrode. Alternatively, the wet powder P may be rolled into a sheet by itself, laminated to the current collector foil 50, and then dried to produce an electrode. Furthermore, the wet powder P may be rolled onto a transfer sheet. The wet powder P may be rolled onto a transfer sheet, laminated to the current collector foil 50 together with the transfer sheet, and then the transfer sheet is removed to produce an electrode.

[0072] The use of the electrode mixture for roll molding of the present embodiment is not particularly limited. It can be used for manufacturing electrodes for non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries, fuel cells, and the like. EXAMPLES

[0073] Hereinafter, a more specific embodiment of the above embodiment will be described. (Examples 1 to 3 and Comparative Examples 1 to 3) Graphite as the negative electrode active material, CNT as the conductive additive, and CMC and SBR as the binder were mixed in the mixing ratio shown in Table 1. Water as a solvent was added to this mixture to prepare a negative electrode mixture slurry with a solid content of about 50 mass %.

[0074] The graphite used as the negative electrode active material had the TAP density and oil absorption shown in Table 1. The oil absorption was measured using linseed oil. The negative electrode mixture slurry was heated to about 80° C. to separate the predetermined solvent, and then crushed to a particle size of about 0.5 mm to 3 mm to prepare wet powder P.

[0075] [Table 1] (Evaluation of the lower limit of solid content without sticking) For each of the wet powders of Examples 1 to 3 and Comparative Examples 1 to 3, the heating time at 80° C. was adjusted to prepare a plurality of wet powders with solid contents differing by about several mass %.

[0076] A plurality of wet powders were roll-formed on the current collector foil 50 using the above-described electrode forming apparatus 1 to form the negative electrode layer 60. The presence or absence of sticking to the first driving roll 11 during roll forming was visually confirmed.

[0077] The roll forming conditions were as follows: Gap between the outer circumferential surfaces of the first driving roll 11 and the second driving roll 12: 300 μm Rotational speed of the first driving roll 11: 12.5 revolutions / min Rotational speed of the second driving roll 12: 25 revolutions / min Thickness of current collector foil: 50μm Among the wet powders that did not stick to the first driving roll 11 during roll forming, the solid content of the wet powder with the smallest solid content was determined as the lower limit of the solid content without sticking (hereinafter, also referred to as the "lower limit of no sticking"). The results are shown in the "lower limit of no sticking (mass%)" column in Table 1.

[0078] (Storage durability test) The negative electrode layer prepared using the wet powder that did not stick to the first driving roll 11 was dried at 80°C to prepare a negative electrode consisting of a current collector foil and a negative electrode active material layer. A lithium ion secondary battery was prepared using this negative electrode. This battery was charged at a constant current and constant voltage to 4.1 V at a current value of 1 / 20 C. After a 10-minute pause, it was discharged at a constant current and constant voltage to 3.0 V at a current value of 1 / 3 C. The discharge capacity at this time was measured and used as the initial capacity.

[0079] Next, the lithium battery was adjusted to SOC100% by charging it to 4.1 V at a current value of 1 / 20 C. This lithium ion secondary battery adjusted to SOC100% was stored in a thermostatic chamber set at 40°C for 14 days.

[0080] The battery was then charged to 4.1 V at a current of 1 / 20 C, and then discharged to 3.0 V at a current of 1 / 3 C at a constant current and voltage, at which the discharge capacity was measured, and the remaining capacity after storage was calculated using the following formula. The results are shown in Table 1.

[0081] Remaining capacity (%) = (battery capacity after high temperature storage / initial capacity) x 100 (Evaluation Results) From Table 1, in Comparative Example 1, the oil absorption of the negative electrode active material was small at 34.3 mL / 100 g, so the lower limit without sticking was large at 83.1 mass %. It is presumed that the active material was damaged because the linear pressure during roll molding was relatively high. The remaining capacity after the storage durability test was 92.4%.

[0082] In Comparative Example 2, the negative electrode active material had a large oil absorption, so the lower limit without sticking was a small value of 70.5 mass %. However, migration occurred in the active material layer after roll molding. The remaining capacity after the storage durability test was 90.9%.

[0083] In Comparative Example 3, the negative electrode active material had a large TAP density. It is presumed that the active material was damaged because the linear pressure during roll molding was relatively high. The remaining capacity after the storage durability test was 92.1%.

[0084] In all of Examples 1 to 3, the lower limit of no sticking was 80 mass % or less. In addition, migration and cracking did not occur in the active material layer after roll molding. It is presumed that the linear pressure during roll molding is relatively low, and damage to the active material layer is suppressed. The remaining capacity after the storage durability test was 96% or more in all cases. [Explanation of symbols]

[0085] 1...electrode forming device, 11...first driving roll, 111...first roll section, 112...first shaft section, 12...second driving roll, 121...second roll section, 122...second shaft section, 50...current collecting foil, 60...electrode layer, 80...supply roll, 90...winding roll, 95...wet powder supplying device, S1..., S1...first surface, S2...second surface, P...wet powder.

Claims

1. An electrode mixture for roll molding containing a solid content including an electrode active material, a binder, and a conductive assistant, and a solvent, The content of the binder in the solid content is 6 mass% or less, and the content of the conductive assistant is 3 mass% or less, The electrode active material has a tap density of 1.3 g / cm 3 and the oil absorption is 40 mL / 100 g or more and 80 mL / 100 g or less, The electrode mixture for roll molding is characterized in that it contains the solid content in a ratio of 70 mass % or more and 80 mass % or less, and the solvent in a ratio of 20 mass % or more and 30 mass % or less.

2. The electrode mixture for roll molding according to claim 1 , wherein the electrode active material is a negative electrode active material and is used for producing a negative electrode.

3. A forming step of roll-forming an electrode layer using the electrode mixture for roll forming according to claim 1; and drying the electrode layer.

4. The method for producing an electrode active material layer according to claim 3 , wherein the electrode layer is a negative electrode layer and is used for producing a negative electrode active material layer.

5. A forming step of roll-forming an electrode layer on a current collector using the electrode mixture for roll forming according to claim 1; and drying the electrode layer.

6. The method for producing an electrode according to claim 5 , wherein the electrode layer is a negative electrode layer and is used for producing a negative electrode.

Citation Information

Patent Citations

  • Nonaqueous secondary battery bilayer structure carbon material and nonaqueous secondary battery anode and nonaqueous secondary battery using the same

    JP2013201125A

  • Carbon material and non-aqueous secondary battery using the carbon material

    JP2014208582A

  • Nonaqueous electrolyte secondary battery

    JP2016225223A

  • Carbonaceous material and nonaqueous secondary cell in which same is used

    WO2014157318A1

  • Carbon material for non-aqueous secondary battery negative electrode, method for producing carbon material for non-aqueous secondary battery negative electrode, and non-aqueous secondary battery

    WO2015146960A1